MASS DEFECT OF STRANGE STARS - Shahinyan, H.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
The mass defect of the strange stars has been studied in the present work. The strange quark matter with minimal energy consisted of u, d, s quarks and electrons was observed in the framework of the bag model. For certain values of the bag parameters the integral parameters for three models of the strange stars with maximal masses twice exceeding sun mass were obtained depending on central density. The dependencies of inner energy Ein and bond energy Δ2M on total mass M for data of the strange star models were presented. It was shown that the packing coefficient of strange stars consisted of strange quark matter is significantly higher than the analogous one of neutron stars.